2016
DOI: 10.1007/s11655-016-2744-2
|View full text |Cite
|
Sign up to set email alerts
|

Liuwei Dihuang Pill (六味地黄丸) Treats Postmenopausal Osteoporosis with Shen (Kidney) Yin Deficiency via Janus Kinase/Signal Transducer and Activator of Transcription Signal Pathway by Up-regulating Cardiotrophin-Like Cytokine Factor 1 Expression

Abstract: The CLCF1 gene is an important gene associated with PMOP Shen-yin deficiency and the therapeutic effects of LDP may be mediated by up-regulation of CLCF1 gene expression and activation of the JAK/STAT signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…In support of the latter hypothesis, CLCF1 was shown to have modest inhibitory effects on osterix expression and mineralization in primary calvarial osteoblast cultures (10). Variations in CLCF1 levels have been recently associated with postmenopausal osteoporosis (11).…”
mentioning
confidence: 77%
“…In support of the latter hypothesis, CLCF1 was shown to have modest inhibitory effects on osterix expression and mineralization in primary calvarial osteoblast cultures (10). Variations in CLCF1 levels have been recently associated with postmenopausal osteoporosis (11).…”
mentioning
confidence: 77%
“…The JAK/STAT signaling pathway plays a vital role in bone metabolism. LWDHP regulates immune function by increasing the expression of the immune-related gene cardiotrophin-like cytokine factor 1 and activation of the JAK/STAT signaling pathway to treat postmenopausal osteoporosis with kidney yin deficiency [ 130 ]. Xia et al suggested that LWDHP could alleviate osteoporosis partially via a significant enhancement in the levels of Lrp-5, β -catenin, Runx2, and Osx, which were involved in the canonical Wnt/ β -catenin signaling pathway of osteoblasts, in osteoporosis model induced by ovariectomy and in vitro experiments [ 131 ].…”
Section: Immunoregulation Mechanisms Of Chinese Medicinal Plants Imentioning
confidence: 99%
“…Therefore, understanding the time and dose effects of ZGP on BMSC osteogenic differentiation will be clinically relevant in the treatment of OP. Although the effect of classic kidney-tonifying compounds on BMSC osteogenic differentiation is still poorly understood, a few preparations such as six-ingredient rehmannia pill, sexoton pill [ 71 , 72 ], Erxian decoction [ 73 ], and Qing'e pill [ 74 ] have been shown to promote osteogenic differentiation and inhibit angiogenic differentiation of BMSCs. Therefore, it is important to compare the effects of the different kidney-tonifying compounds on BMSC osteogenic differentiation vis-à-vis OP treatment.…”
Section: Future Directions?mentioning
confidence: 99%